Agglomeration Economies or Selection? An Analysis of Taiwanese Science Parks. (May 2018) - Hasan, Syed; Faggian, Alessandra; Klaiber, H. Allen; Sheldon, Ian
Agglomeration spillovers are a major driver of policy creating science parks across the world. However, agglomeration benefits may be offset by competition arising out of spatial proximity of firms. Analysis of Taiwanese firms' total factor productivity distribution shows that, depending on location choice, the impact of agglomeration and selection is heterogeneous across firm types. Spatial analysis is applied to evaluate the regional innovation policy of establishing science parks. A sectoral analysis of productivity distributions reveals that there is a positive relationship between technology intensity of the production process and firm productivity levels when firms are located in science parks.